To Invest, Or Not to Invest, That Is the Question Investment Preferences Among Business Students - Rafał BUŁA; Paulina WOJTALA (Communications of International Proceedings, 2021)
Aim/Purpose – The main purpose of the paper is to determine the nature of influence of various socio-economic and demographic factors on investment preferences of business students. The study also aims at revealing connections between variables describing students’ involvement in their education process at business schools and their investment attitude and behaviors. Design/methodology/approach – Those problems are investigated using statistical approach and methods: analysis of contingency tables due to nominal character of many factors considered as well as non-parametric analogues of standard ANOVA tests (e.g., Mann-Whitney, Kruskal-Wallis and Friedman tests supported by post-hoc analyses). The analyzed data were gathered by spreading an on-line questionnaire including questions regarding interviewees’ investment preferences among all the students of the University of Economics in Katowice in the period of January 13, 2021-February 7, 2021. Findings – The findings show that socio-economic and demographic factors affect investment perception, attitude, and decisions in different ways. Gender is the most influential variable among the investigated factors – it is proven that males are more risk-seeking than females, show more interest in investing, and as a result, their knowledge about investments is more grounded. From the purely teaching point of view, among the most important factors influencing students’ investment knowledge is their field of study, which may suggest undertaking additional efforts to eliminate those differences. Research implications/limitations – Our findings indicate that the most important factor differentiating students’ investment attitude and interest is gender. However, their knowledge about investing also depends heavily on the field of study, which could be a signal that more intensive efforts (e.g., additional courses) are needed to improve their investment knowledge and skills. Originality/value/contribution – The paper is relevant as it reveals the impact of particular socio-economic and demographic factors on students’ investment preferences, knowledge, and behavior, which are crucial to their future decisions regarding personal finance. The findings can also serve as a guideline while implementing any changes in teaching process in the field of investments.
Keywords: Investments; Business Students; Investment Preferences.